2015
DOI: 10.15306/mvpjms/2015/v2i2/78300
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Blue Prints for formative Theory Assessment of Undergraduate Medical Students in Community Medicine

Abstract: The written assessment of medical students is very important in view of assessing the various levels of cognitive domains. The validity of any assessment depends upon the appropriate constriction of assessment tool. Framing an ideal theory assessment tool that covers the whole syllabus with proportionate weightage to various content areas according to their importance is big challenge for the paper setter. Considering the vast nature of Community Medicine syllabus constructing a theory assessment tool as per a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A The number and type of questions to be asked from a particular topic and the allotted marks is calculated by blueprinting as done with format-1 in the present work. 5 For blueprinting we assign the impact score and frequency score to each content area and calculate the weightage to be given. The impact score (I) is based on the importance of topic.…”
Section: Example 1: Structured Laq (Problem Based)mentioning
confidence: 99%
“…A The number and type of questions to be asked from a particular topic and the allotted marks is calculated by blueprinting as done with format-1 in the present work. 5 For blueprinting we assign the impact score and frequency score to each content area and calculate the weightage to be given. The impact score (I) is based on the importance of topic.…”
Section: Example 1: Structured Laq (Problem Based)mentioning
confidence: 99%
“…The blue print procedure adopted was similar to a study done in the subject of community medicine (Gujarathi et al, 2015). When Analysis of the papers in different subjects was done, it was found that all subtopics and all domains of a subject were not represented.…”
Section: Figure 2: Comparison Of Percentage Scores Of Pre-test and Pomentioning
confidence: 99%